The Role of Virtual Reality in Cancer Pain Management: A Systematic Literature Review - Ignatia Novianti Tantri; Riyadh Firdaus; Tasya Claudia Pardede; Aida Rosita Tantri; Sidharta Kusuma Manggala (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Virtual reality (VR) is a 3D environment-based simulation using computer technology that creates a realistic multi-sensorial experience. VR allows users to simulate real-world scenarios in a safe, attractive virtual space. Immersive VR has been proposed as a non-pharmacologic approach to cancer pain management. This systematic review aimed to explore the role of virtual reality in cancer pain management. Methods: The current review was conducted and reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. This study used PICO consisting of population: adult patients with cancer pain, intervention: virtual reality, comparison: placebo, outcome: reducing cancer pain. Results: Four studies of moderate to the high quality that met the inclusion and exclusion criteria were reviewed in this study. Two studies show VR can reduce stress and anxiety and increase relaxation. Two RCTs demonstrated the effectiveness of VR in reducing cancer pain. Conclusion: Virtual reality technology can help to reduce cancer pain. In addition to pain severity, other parameters such as fatigue, depression, anxiety, and stress also were decreased. VR also could increase the level of relaxation. Virtual reality's role in reducing pain can have good implications for cancer pain management and increasing patient comfort.